Genome-wide association of trypanosome infection status in the tsetse fly Glossina fuscipes, the major vector of African trypanosomiasis in Uganda - Saarman, Norah; Son, Jae Hak; Zhao, Hongyu; Cosme, Luciano; Kong, Yong; Li, Mo; Wang, Shiyu; Weiss, Brian; Echodu, Richard; Opiro, Robert; Aksoy, Serap; Caccone, Adalgisa (Research Square, 2022)
The primary vector of the trypanosome parasite causing human and animal African trypanosomiasis in Uganda is the riverine tsetse fly Glossina fuscipes fuscipes (Gff). We conducted a genome-wide association (GWA) analysis with field-caught Gff. To increase statistical power, we first improved the Gff genome assembly with whole genome 10X Chromium sequencing, used ddRAD-seq to identify autosomal versus sex-chromosomal regions of the genome with data from 96,965 SNPs, and conducted a GWA with a subset of 50,960 autosomal SNPs from 351 flies. Results assigned a full third of the genome to the sex chromosome, suggested possible sex-chromosome aneuploidy in Gff, and identified a single autosomal SNP to be highly associated with trypanosome infection. The top SNP was ~ 1200 bp upstream of the gene lecithin cholesterol acyltransferase (LCAT), an important component of the molecular pathway that initiates trypanosome lysis and protection in mammals. Results indicate that variation upstream of LCAT and/or linked genetic elements are associated with trypanosome infection susceptibility in Gff. This suggests that there may be naturally occurring genetic variation in Gff that can protect against trypanosome infection, thereby paving the way for targeted research into novel vector control strategies that can promote parasite resistance in natural populations.
Keywords: ddRAD; Trypanosomiasis; Vector; Genome wide association; GWAS; Population genomics; Muller elements; Chromosome arms; Aneuploidy